Directly acting antivirals for hepatitis C virus arrive in HIV/hepatitis C virus co-infected patients: from 'mind the gap' to 'where's the gap?'. (24th April 2016) - Childs, Kate; Taylor, Chris; Dieterich, Douglas; Agarwal, Kosh
Abstract : In patients living with HIV infection with hepatitis C (HCV) is common. HIV/HCV co-infection results in more rapid liver fibrosis progression than HCV alone and end-stage liver disease is a major cause of morbidity and mortality in co-infected patients. Historically, treatment outcomes with interferon based therapy in this group have been poor but with the advent of directly acting antiviral (DAA) drugs for HCV, rates of cure have improved dramatically. This article reviews recent evidence on the treatment of HCV in co-infected patients including the efficacy of new regimens and information on drug–drug interactions between DAAs and antiretroviral therapy. We also discuss the relationship between the pathogenesis of HIV and HCV infections, the treatment of acute hepatitis C and the current debate regarding the cost-effectiveness and affordability of DAAs.